Antidiabetic Phytochemicals From Medicinal Plants: Prospective Candidates for New Drug Discovery and Development - Alam, Safaet; Sarker, Md. Moklesur Rahman; Sultana, Taposhi Nahid; Chowdhury, Md. Nafees Rahman; Rashid, Mohammad A.; Chaity, Nusrat Islam; Zhao, Chao; Xiao, Jianbo; Hafez, Elsayed E.; Khan, Shah Alam; Mohamed, Isa Naina (Frontiers in Endocrinology, 2022)
Diabetes, a chronic physiological dysfunction affecting people of different age groups and severely disturbs the harmony of peoples’ normal life worldwide. In spite of the availability of insulin preparations and several synthetic oral antidiabetic drugs, there is a crucial need for the discovery and development of novel antidiabetic drugs because of the occurrence of resistance development and side effects of those drugs in long-term use. On the contrary, plants or herbal sources are getting popular to the scientists, researchers, and pharmaceutical companies all over the world day by day to search for potential bioactive compound(s) for the discovery and development of targeted novel therapeutics of antidiabetic drugs which will control diabetes with the least unwanted effects of the conventional antidiabetic drugs. In this review, we have presented the prospective candidates comprised of either isolated phytochemical(s) or extract(s) containing bioactive phytoconstituents which have been reported in several in vitro, in vivo, and clinical studies possessing noteworthy antidiabetic potential. The mode of actions, attributed to antidiabetic activities of the reported phytochemicals or plant extracts have also been described to highlight and focus on the prospective phytochemicals and phytosources for further studies in the discovery and development of novel antidiabetic therapeutics.